2021
DOI: 10.3390/jpm11070623
|View full text |Cite
|
Sign up to set email alerts
|

Moving towards Integrated and Personalized Care in Parkinson’s Disease: A Framework Proposal for Training Parkinson Nurses

Abstract: Delivering healthcare to people living with Parkinson’s disease (PD) may be challenging in face of differentiated care needs during a PD journey and a growing complexity. In this regard, integrative care models may foster flexible solutions on patients’ care needs whereas Parkinson Nurses (PN) may be pivotal facilitators. However, at present hardly any training opportunities tailored to the care priorities of PD-patients are to be found for nurses. Following a conceptual approach, this article aims at setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 93 publications
(154 reference statements)
1
21
0
Order By: Relevance
“…Their role therefore promotes shared decision-making and contribute to personalizing the care pathway. Our findings align with recent literature on the role of specialized nurses as facilitators with expert skills within integrated care networks [ 2 ], [ 32 ]. A single point of contact and navigation tools are indispensable for the constitution of an integrated care network and the stabilization of the network over time by supporting a “system of navigation and alliances” inside the network [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…Their role therefore promotes shared decision-making and contribute to personalizing the care pathway. Our findings align with recent literature on the role of specialized nurses as facilitators with expert skills within integrated care networks [ 2 ], [ 32 ]. A single point of contact and navigation tools are indispensable for the constitution of an integrated care network and the stabilization of the network over time by supporting a “system of navigation and alliances” inside the network [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…As reflected in our data, the transition into a nursing home can be a massive relief for the caregivers. Because the cases of late-stage PD are going to increase during the next years and a trend towards a more personalized care evolves [ 61 ], research about more specialized nursing homes and their influence on disease progression and satisfaction, as well as its influence on the caregivers, is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence programs should be tailored to address this thin balance and move towards more patient-centric interventions that not only elicit patients' input but also understand and allow the need for modifying dosage at varied times under clinician's guidance. Earlier studies have shown that an integrated, individualized approach is especially favorable for patients with changing needs due to unpredictable disease status such as Parkinson's and autoimmune diseases, including RA [56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%